2020
DOI: 10.1038/s41589-020-00696-0
|View full text |Cite
|
Sign up to set email alerts
|

Linkage-specific ubiquitin chain formation depends on a lysine hydrocarbon ruler

Abstract: Virtually all aspects of cell biology are regulated by a ubiquitin code where distinct ubiquitin chain architectures guide the binding events and itineraries of modified substrates. Various combinations of E2 and E3 enzymes accomplish chain formation by forging isopeptide bonds between the C-terminus of their transiently-linked donor ubiquitin and a specific nucleophilic amino acid on the acceptor ubiquitin, yet it is unknown whether the fundamental feature of most acceptors - the lysine side-chain - affects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 60 publications
2
34
1
Order By: Relevance
“…To test this hypothesis, we first measured the binding affinity for each of these substituted variants using biolayer interferometry (BLI). Previous studies found a K m for the acceptor Ub to UBE2R2 to be ~500 μM (Liwocha et al, 2021), within error of our observed K d value for wild-type UBE2R2 of 650 μM AE 140 μM (Fig 4 A). Both D143K and R149E variants had significantly reduced binding with K d values of ~2 mM and > 4 mM, respectively (Figs 4A and EV3C and D).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…To test this hypothesis, we first measured the binding affinity for each of these substituted variants using biolayer interferometry (BLI). Previous studies found a K m for the acceptor Ub to UBE2R2 to be ~500 μM (Liwocha et al, 2021), within error of our observed K d value for wild-type UBE2R2 of 650 μM AE 140 μM (Fig 4 A). Both D143K and R149E variants had significantly reduced binding with K d values of ~2 mM and > 4 mM, respectively (Figs 4A and EV3C and D).…”
supporting
confidence: 89%
“…Furthermore, we expect that this mutation could impact the enzymatic activity of the E2, as the gate loop is thought to aid in catalysis by partially stabilizing the tetrahedral oxyanion intermediate (Jones et al, 2019). A recent study showed that a similar subtle change resulted in a drastic K m and k cat defect when the Ub K48 side chain was synthetically increased in length by a single methylene (Liwocha et al, 2021).…”
mentioning
confidence: 99%
“…A recent study by Schulman et al aimed to investigate whether the lysine chain length of the acceptor Ub plays a role in E2/E3 mediated catalysis. 124 Mutation of key Ub lysine sites with shorter and longer lysine analogues and subsequent enzymatic analysis with E2/E3 illustrated that the side chain geometry can strongly impact polyubiquitylating enzymes (Fig. 8, Chain length).…”
Section: Lysine Ubiquitination and Sumoylationmentioning
confidence: 99%
“…In ar ecent study into the mechanism of Ub chain formation catalyzed by distinct Ub-carrying E2/E3 enzyme (e.g.,U BE2G1, Rsp5p), the removal or addition of only as ingle methylene from or onto the aliphatic acceptor Ub lysine side chain was found to strongly influence the linkagespecific Ub chain formation (the so-called "lysine hydrocarbon ruler"). [15] This observation suggests that the E3 activity is sensitive to the architecture surrounding E2-Ub conjugation site.H owever,t he Ub C-terminal residues (Arg74 and Gly75) of Virdeesp robe had to be replaced with atriazole, [10a] and three extra bonds were needed for the backbone between the carbonyl-carbon of Ub-Gly75 and bcarbon of the E2 catalytic Cys side chain of SchulmansE2Ub probe (Figure 1b). [10f] Therefore,wesought to develop anew activity-based E2-Ub probe by replacing the catalytic Cys of E2 with Dap,a nd introducing aD ha at position 76 of the Ub.…”
Section: Introductionmentioning
confidence: 98%